Implementation Of Pandemic Prevention Policy In The Police - Adipta Wisnu Wardhani; Sumartono, Sumartono; Abdullah Said; Hermawan, Hermawan (CV. AFDIFAL MAJU BERKAH, 2023)
The purpose of this research is the implementation of the policy of Presidential Decree No. 7 of 2020 in an effort to prevent the Pandemic at the National Police Headquarters, the impact of implementing policies to prevent the spread of the Pandemic at the National Police Headquarters and the model of implementing policies at the National Police Headquarters in preventing the spread of the Pandemic. This research is qualitative because to maintain regularity and consistency. The results of the study indicate that the implementation of the policies set at the National Police Headquarters is to maintain a distance and a ban on traveling out of town. Meanwhile, the impact of this implementation is the increase in the duties of personnel at the National Police Headquarters due to the implementation of social distancing protocols during the pandemic, resulting in high crime. The Merilee S. Grindle model used to assess the success of implementation is influenced by two major variables, namely the content of the policy and the implementation environment. The type of policy implementation that is in accordance with the program to accelerate the handling of Covid-19 is substantive and procedural politics